Analisis Praktik Akad Syirkah di PT. Yotta Berkah Mulia Makassar dalam Perspektif Hukum Ekonomi Syariah - Kurniawan, Anjas; Mayo, Abbas Ali; S, Subaedah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this research is to understand the practice of the Syirkah contract at PT. Yotta Berkah Mulia and to evaluate the perspective of Islamic Economic Law on the Syirkah practices at PT. Yotta Berkah Mulia Makassar. This research employs a qualitative method with a descriptive approach. Data sources were obtained from primary and secondary sources. Data collection was conducted using observation, interviews, and documentation methods. The data analysis was carried out in four stages: data description, data reduction, data presentation, and conclusion drawing. The findings show that the Syirkah contract is implemented between two parties in partnership: PT. Yotta Berkah Mulia and the Yotta Investor. The contract is established when the partners agree to the terms and conditions outlined by the company.The capital provided by PT. Yotta Berkah Mulia is in the form of Standard Operating Procedures (SOPs) and business facilities, while the capital from the Yotta Investor is in the form of money. The profit-sharing system is as follows: 50% for PT. Yotta Berkah Mulia and 50% for the Yotta Investor. In case of a loss, it will be borne proportionally based on the capital contributed by each party, except if the loss is caused by negligence on the part of one of the parties.The responsibilities of the Yotta Investor include: Contributing the agreed-upon capital and Providing suggestions and recommendations for business development.Meanwhile, the responsibilities of PT. Yotta Berkah Mulia include:Managing and operating the business professionally and Keeping transparent financial records and reporting business performance to the Yotta Investor.